A stereo-selective growth inhibition profile of ginsenoside Rh2 on human colon cancer cells. Issue 1 (1st January 2019) - Jeong, Yunju; Ku, Seockmo; You, Hyun Ju; Ji, Geun Eog
ABSTRACT: We compared the stereo-selective growth inhibition effects of purified enantiomeric pairs of ginsenoside Rh2 (20(S)-ginsenoside Rh2 and 20(R)-ginsenoside Rh2) on human colon cancer cells in vitro with non-invasive real-time cellular analysis. When 50 μM, respectively, of 20(S)-ginsenoside Rh2 and 20(R)-ginsenoside Rh2 were administered to the colon cancer cell line HT-29, only the S-type ginsenoside Rh2 lowered cancer cell viability. Similarly, when the same experiment was conducted on cancer cells with different levels of ginsenoside treatments (20, 40, 60, and 80 μM), cancer cell viability was decreased in a dose-dependent manner only in the 20(S)-ginsenoside Rh2 treatment groups. Cytotoxicity of cancer cells was observed only in the S form-treated group when cellular response and growth pattern were analyzed via real-time cellular analysis. These findings suggest that the anti-tumor effect of ginsenoside Rh2 on colon cancer cells is S-form selective.